Gender Differences in Dengue Fever Incidence in Semarang City: Data Analysis from 2019-2021 - Fedhilla, Fiona Syahri; Ariska, Moudy Bella (BKM Public Health and Community Medicine, 2024)
Purpose: Dengue virus infection is a major health issue in tropical countries, commonly transmitted by Aedes aegypti mosquitoes. It can cause asymptomatic or symptomatic infections, with symptoms ranging from mild to severe. This study aims to describe the incidence of Dengue Hemorrhagic Fever (DHF) by gender in Semarang City, using data from 2019 to 2021. Methods: A descriptive study was conducted using secondary data obtained from the Semarang City Health Department and the Ministry of Health of the Republic of Indonesia. Results: The study revealed significant fluctuations in DHF incidence in Semarang City over the study period. There was an increase in cases each year, peaking in 2021. Despite this, the mortality rate from DHF remained relatively low and fluctuated over the years. Risk factors influencing DHF incidence included gender, with higher incidence rates observed in males compared to females. Activity patterns and environmental exposure were critical factors affecting gender DHF transmission risk. Preventive behaviors also played a significant role, where public education on effective preventive measures could help reduce transmission risk. Conclusion: This study indicates that the fluctuating incidence of DHF in Semarang City requires more effective and targeted preventive measures. Strengthening prevention programs, vector control, and public education are essential to reducing the burden of this disease. Further research is needed to understand the factors influencing the fluctuation in DHF cases between males and females to formulate more effective and focused prevention strategies. Thus, it is hoped that the negative impact of DHF on the Semarang community can be reduced, improving their well-being and quality of life.